1988
DOI: 10.5935/0305-7518.19880026
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine and dapsone compliance in leprosy

Abstract: SummaryThe regularity with which multi bacillary patients, who were being treated with the WHO Study Group regimen in a THELEP-sponsored field trial in South India, ingested their prescribed daily clofazimine and dapsone was studied. The ingestion of clofazimine was monitored using a specially prepared fo rmulation containing minute amounts of isoniazid as an innocuous marker. Overall drug acceptability and compliance was excellent. Approximately 75% of the prescribed daily clofazimine and dapsone doses were b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…[28] With MDT, the adherence was only 70–80%. [29] However, to accelerate leprosy elimination process, recently the WHO leprosy programme and its TAG have changed dramatically their position on supervised therapy. They concluded that after the first dose of MDT “supervision of the subsequent monthly component of the MDT regimens is no longer essential.“[30] Further, on the basis of this conclusion they recommended large-scale implementation of accompanied multidrug therapy (AMDT), which refers to a policy that patients are provided the entire supply of MDT drugs at the time of diagnosis, when choosing someone close to them to accompany them with their treatment.…”
Section: Who Therapy and Its Impactmentioning
confidence: 99%
“…[28] With MDT, the adherence was only 70–80%. [29] However, to accelerate leprosy elimination process, recently the WHO leprosy programme and its TAG have changed dramatically their position on supervised therapy. They concluded that after the first dose of MDT “supervision of the subsequent monthly component of the MDT regimens is no longer essential.“[30] Further, on the basis of this conclusion they recommended large-scale implementation of accompanied multidrug therapy (AMDT), which refers to a policy that patients are provided the entire supply of MDT drugs at the time of diagnosis, when choosing someone close to them to accompany them with their treatment.…”
Section: Who Therapy and Its Impactmentioning
confidence: 99%
“…The major objective of combining RMP with DDS and CLO is to ensure the elimination of spontaneously occurring RMP-resistant mutants before stopping chemotherapy (14). However, even in the best leprosy control program, it is difficult to persuade patients to adhere to the self-administered daily therapy (3), suggesting that RMP resistance may still develop if the DDS-CLO component is not taken regularly. RMP resistance might be reduced if a fully supervised, monthly administered MDT regimen can be developed, i.e., if all of the components are given under supervision once monthly.…”
mentioning
confidence: 99%
“…For example, patients often neglect their treatments, because clofazimine causes stigmatizing skin discoloration or they become weary of the length of treatment. 13,14 The largest reported study is a 6-y follow up of 47,276 patients conducted in China, which revealed an overall relapse rate of 0.73/1,000 person-years [with the risk of PB patient relapse (1.04/1,000 person-years) significantly greater than that for MB patients (0.61/1,000 personyears)]. 15,16 A 10-y prospective study in the Philippines observed an overall relapse rate equivalent to 2.8/1,000 person-years.…”
Section: Need For a Leprosy Vaccinementioning
confidence: 99%